2010
DOI: 10.2135/cropsci2009.09.0479
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance and Recovery of Kentucky Bluegrass Subjected to Seasonal Wear

Abstract: Kentucky bluegrass (Poa pratensis L.) is frequently established on sports fields that receive wear during one or more seasons. Differences exist among Kentucky bluegrass cultivars for seasonal performance characteristics such as spring green‐up and summer stress tolerance. The objective of this study was to determine whether the wear tolerance and recovery of Kentucky bluegrass cultivars were dependent on season. Twenty‐two Kentucky bluegrass cultivars, representing nine genetically diverse Kentucky bluegrass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 11 publications
0
18
0
Order By: Relevance
“…However, the cost of inputs increases linearly with the application rate. This creates an agronomic optimum level of intensification where the marginal benefits of another kilogram of nitrogen equal the marginal costs (Park et al 2010). Yield at the agronomic optimum may well be less than the attainable yield and is likely to be significantly less than the biophysical maximum.…”
Section: Implications For Sustainable Intensification and Closure Of mentioning
confidence: 99%
“…However, the cost of inputs increases linearly with the application rate. This creates an agronomic optimum level of intensification where the marginal benefits of another kilogram of nitrogen equal the marginal costs (Park et al 2010). Yield at the agronomic optimum may well be less than the attainable yield and is likely to be significantly less than the biophysical maximum.…”
Section: Implications For Sustainable Intensification and Closure Of mentioning
confidence: 99%
“…This score is usually based on a nine-level scale (Martiniello, 2007) or 0-100% scale (Park et al, 2010). Although relevant information can be collected from these types of studies, the resultant data can be variable and difficult to reproduce by other investigators (Richardson et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…This analysis is recognized as being more reproducible and less laboursome and time-consuming than traditional techniques of quantitative or subjective analysis (Ghalia et al, 2012;Richardson et al, 2001). The turf cover in wear tolerance experiments is usually presented as the absolute value of the trafficked plot (Thoms et al, 2011) or as the difference between trafficked vs. non-trafficked plots (Park et al, 2010). The authors propose new parameters expressing turf cover and quality.…”
Section: Discussionmentioning
confidence: 99%
“…St. Augustine grass [ Stenotaphrum secundatum (Walter) Kuntze] (62 N m) and seashore paspalum ( Paspalum vaginatum Sw.) (65 N m) had roughly the same traction readings between the highest and lowest traction groups cited above. Park et al (2010) assessed wear tolerance as the loss or recovery of canopy density and found seasonal differences for wear tolerance in Kentucky bluegrass. The greatest reduction in density occurred in the fall, whereas greater recovery potential was noticed during fall and spring.…”
Section: Sports Turf Playability and Wearmentioning
confidence: 99%